P Peningkatan Kesadaran dan Pencegahan Skabies Melalui Program Promosi Kesehatan di Puskesmas Banjarbaru Selatan: Raising Awareness and Prevention of Scabies Through Health Promotion Programs at the South Banjarbaru Health - Ramadhana, Desy Yolanda Wulan; Mardiati, Nurul; Kurniasih, Endang (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2025)
Scabies, caused by the infestation of the mite Sarcoptes scabiei var hominis, remains a significant health problem in Indonesia, especially in areas with inadequate sanitation. This community service aims to increase public awareness of scabies through a health promotion program implemented at the Banjarbaru Selatan Health Center. The health promotion method includes administering a pre-test, delivering material orally, interactive discussions, distributing educational leaflets, and evaluating through a post-test. This activity was attended by 15 participants from the general public at Posyandu Seruni on June 13, 2024. The measurement was conducted using a questionnaire, with pre-test results showing an average knowledge score of 77.3%, which increased to 91.33% after the activity. This improvement reflects the effectiveness of the delivery method and media used. Based on data analysis, several statements showed a significant increase in understanding, particularly about the use of scabies medication and the symptoms of the disease. The high enthusiasm of participants during the discussion session also contributed to the effectiveness of the activity. These results indicate that health promotion programs can contribute to increasing public awareness of scabies and motivate them to take preventive measures. It is recommended that future scabies education focus on the procedures for managing scabies, including treatment, skin care, and prevention of transmission, so that participants can effectively address and prevent the disease. With these measures, it is hoped that the prevalence of scabies in the community will decrease, thereby improving overall health quality.